Combined application of mica waste and Bacillus pseudomycoides as a potassium solubilizing bio-fertilizer reduced the dose of potassium fertilizer in tea-growing soil. Issue 5 (28th May 2021) - Pramanik, Prabhat; Kalita, Chayanika; Borah, Krishna; Kalita, Pallabi
ABSTRACT: Potassium-solubilizing bacteria (KSB) are often used in the field of vegetable and horticultural crops. In this study, a strain of Bacillus pseudomycoides was used as the KSB strain and different combinations of muriate of potash (MoP) and mica waste (MW) along with that strain were applied in soil to evaluate its effect on exchangeable K content in soil and yield of tea shoots. The objective of this experiment was to evaluate the possibility of applying an indigenous KSB strain and MW combination for reducing doses of MoP during cultivation of perennial crops like tea. The study over two consecutive years revealed that cumulative tea production of some of the applied treatments was significantly higher than that of recommended MoP treatment. Application of KSB and MW in the first split instead of MoP recorded higher exchangeable K content in soil during August to October, especially in the second year of the study. The study confirmed B. pseudomycoides can be used as a KSB biofertilizer in soil and application of MW and KSB combined replacing MoP in the first split could be economical as well as improving K use-efficiency in soil and increased yield and K-uptake by the plants.